Exploring detection of contact vs. fantasy online sexual offenders in chats with minors: Statistical discourse analysis of self-disclosure and emotion words. (July 2018) - Chiu, Ming Ming; Seigfried-Spellar, Kathryn C.; Ringenberg, Tatiana R.
Abstract: This exploratory study is the first to identify content differences between youths' online chats with contact child sex offenders (CCSOs; seek to meet with youths) and those with fantasy child sex offenders (FCSOs; do not meet with youths) using statistical discourse analysis (SDA). Past studies suggest that CCSOs share their experiences and emotions with targeted youths (self-disclosure grooming tactic) and encourage them to reciprocate, to build trust and closer relationships through a cycle of self-disclosures. In this study, we examined 36, 029 words in 4, 353 messages within 107 anonymized online chat sessions by 21 people, specifically 12 youths and 9 arrested sex offenders (5 CCSOs and 4 FCSOs), using SDA. Results showed that CCSOs were more likely than FCSOs to write online messages with specific words (first person pronouns, negative emotions and positive emotions), suggesting the use of self-disclosure grooming tactics. CCSO's self-disclosure messages elicited corresponding self-disclosure messages from their targeted youths. These results suggest that CCSOs use grooming tactics that help engender youths' trust to meet in the physical world, but FCSOs do not.